Penerapan Metode Buffer Stock dalam Prediksi Ketercukupan Bahan Baku - Elsa Violina Damayanti; Muhammad Arifin; Syafiul Muzid; Yudie Irawan (Universitas Budi Darma, 2023)
UD. Elvajaya has sales and purchases of stock of bag raw materials, but until now UD. Elvajaya experienced difficulties in terms of predicting or estimating the calculation of raw materials according to incoming orders. Raw materials often experience advantages and disadvantages in the ongoing process of making bags, causing service to customers to experience delays in the process of making and shipping goods to be delayed. The absence of proper calculations when there is an incoming order results in an unstable stock of raw materials with the number of incoming orders. In making raw material reports, books are still used as storage so that raw materials are not controlled. This study proposes the application of the buffer stock method to overcome existing problems. With the existence of a prediction system for the adequacy of raw materials using the buffer stock method, it can assist in the process of calculating raw materials to be purchased according to incoming orders so as to reduce the risk of stock shortages in the ongoing manufacturing process. The buffer stock method has several advantages, namely, minimizing risks in production regarding insufficient raw materials, being able to handle ordering requests with quite a large number. With this system, it is hoped that the problems faced by UD owners can be resolved. This research produces a prediction of how many raw materials will be issued for the following month by looking at the bag orders in the previous month. UD.Elvajaya produces 1440 cm of Buffer Stock for fabric raw materials, 1440 cm of zippers, 2160 cm of hose, 2160 cm of bisban, 15 threads, and 44 zipper heads.Â